2022
DOI: 10.2334/josnusd.21-0433
|View full text |Cite
|
Sign up to set email alerts
|

Coronal and apical leakage among five endodontic sealers

Abstract: Purpose:The aim of this study was to use dye penetration to measure apical and coronal leakage simultaneously in single-canal teeth that had been treated endodontically using a single-cone obturation technique. Methods: One hundred single-canal, extracted human teeth were cleaned and shaped with ProTaper NEXT rotary files to size-X5 (50/.06), then randomly assigned to five sealer groups for single-cone gutta-percha obturation. The teeth were soaked in 0.6% rhodamine B at 37°C for seven days, then the roots wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
4
0
3
Order By: Relevance
“…Dye penetration and SEM were applied in this study to analyze microleakages. Dye penetration was the most common approach for measuring apical or coronal microleakages of different obturation systems because it is easy to perform [ 35 , 36 ]. A previous study reported some drawbacks of dye penetration method and that its results may be influenced by other factors, such as the physical process of diffusion, filtration, and capillarity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dye penetration and SEM were applied in this study to analyze microleakages. Dye penetration was the most common approach for measuring apical or coronal microleakages of different obturation systems because it is easy to perform [ 35 , 36 ]. A previous study reported some drawbacks of dye penetration method and that its results may be influenced by other factors, such as the physical process of diffusion, filtration, and capillarity [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted up to thirty to seventy-five days of the observation period for the bacterial leakage [ 17 , 18 ], however our study only involved twenty-five days since there were no more bacterial leakage occurred after twenty-five days. As coronal leakage is faster than apical leakage [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 a & Additional file 2 : S2a), we believe that curved root canals may be one of the obstacles to achieving high apical sealer penetration in clinical practise. Moreover, there are other reasons that may have a very large effect on the penetration of sealers, including the diameter of the root canal, the type of irrigants, the concentration and volume of the irrigants, obturation techniques, and the different filling materials [ 13 , 32 – 34 ]. These factors may also become one of the possible reasons why some studies have reported that SI produces no obvious contrast in tubular dentin sealer penetration compared with CNI in the apical third of the root canal [ 10 , 24 , 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%